Dancing tango : passionate encounters in a globalizing world - Davis, Kathy, 1949- (New York University Press, 2015)
"Argentinean tango is a global phenomenon. Since its origin among immigrants from the slums of Buenos Aires and Montevideo, it has crossed and re-crossed many borders. Yet, never before has tango been danced by so many people and in so many different places as today. Argentinean tango is more than a specific music and style of dancing. It is also a cultural imaginary which embodies intense passion, hyper-heterosexuality, and dangerous exoticism. In the wake of its latest revival, tango has become both a cultural symbol of Argentinean national identity and a transnational cultural space in which a modest, yet growing number of dancers from different parts of the globe meet on the dance floor. Through interviews and ethnographical research in Amsterdam and Buenos Aires, Kathy Davis shows why a dance from another era and another place appeals to men and women from different parts of the world and what happens to them as they become caught up in the tango salon culture. She shows how they negotiate the ambivalences, contradictions, and hierarchies of gender, sexuality, and global relations of power between North and South in which Argentinean tango is - and has always been - embroiled. Davis also explores her uneasiness about her own passion for a dance which - when seen through the lens of contemporary critical feminist and postcolonial theories - seems, at best, odd, and, at worst, disreputable and even a bit shameful. She uses the disjuncture between the incorrect pleasures and complicated politics of dancing tango as a resource for exploring the workings of passion as experience, as performance, and as cultural discourse. She concludes that dancing tango should be viewed less as a love/hate embrace with colonial overtones than a passionate encounter across many different borders between dancers who share a desire for difference and a taste of the 'elsewhere.'Dancing Tango is a vivid, intriguing account of an important global cultural phenomenon"--